Adaptive observer protocol designs for consensus tracking of multi‐agent systems. Issue 13 (7th June 2022) - Chu, Hongjun; Gorbachev, Sergey; Yue, Dong; Dou, Chunxia; Ge, Yuan
Abstract: In this brief, a type of novel fully distributed adaptive protocols is designed for achieving leader‐follower multi‐agents tracking. The design procedure constitutes three steps. First, a local observer is constructed for each agent (including the leader) in virtue of its own inputs and outputs, aiming to estimating of that agent's state. Second, to propagate the estimate of the leader from target followers to all the followers, a distributed adaptive estimator is then proposed, via embedding with time‐varying coupling weights. At last, an elegant controller is designed for each follower based on the estimate of its own state and the estimate of the leader's state. The rigorous convergence analysis is provided. Finally, the simulation results validate the effectiveness of the proposed protocols.